4 practice tests for the TOEFL. - Kaplan Publishing (New York, NY : Kaplan Publishing, 2020)
Kaplan's 4 Practice Tests for the TOEFL provides printed exams and expert explanations to help you master your English abilities in reading, writing, listening, and speaking. Test-like Listening tracks, realistic practice questions, and additional online resources give you everything you need to succeed on the TOEFL. The Most Practice Four full-length practice exams in the book and online Exam-like questions with detailed answer explanations help you build your Listening, Reading, Speaking, and Writing skills Listening tracks for test-like practice online Expert Guidance We know the test: The Kaplan team ensures our practice questions and study materials are true to the test. Kaplan's books and practice questions are written by experts who know students--every explanation is written to help you learn. We invented test prep--Kaplan (www.kaptest.com) has been helping students for 80 years, and our proven strategies have helped legions of students achieve their dreams.
Keywords: Test of English as a Foreign Language -- Study guides; English language -- Examinations -- Study guides; English language -- Textbooks for foreign speakers